How to measure the economic integrity of IBOR panels? A behavioural approach - Mielus, Piotr (Jak mierzyć ekonomiczną spójność paneli typu IBOR? Podejście behawioralne, 2019)
IBOR manipulation imposed new benchmark regulations that forced the market to enter a path of the reform of the existing financial indices and the creation of new ones. The paper describes the evolution of two IBOR panels: one representing a global financial benchmark LIBOR, and the other representing a local PLN benchmark, WIBOR. The paper provides a quantitative analysis of partial quotes of IBOR panellists and suggests that economic integrity measures should be introduced for IBOR panels. The aim of the research is to define a set of tools that provide information regarding the efficiency of the process of the production of the interest rate benchmark. The research is supplemented with a behavioural analysis of the banks’ decision-making process that interferes the contribution of IBOR data. The integrity measures can help market users and financial authorities in evaluating the quality of current and past panels and identifying behavioural factors impacting on partial quotes of the contributing banks.
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 1, s. 51-73
Keywords: financial benchmarks; money market; behavioural finance; wskaźniki rynku finansowego; rynek pieniężny; finanse behawioralne